Cocaine Positivity in ST-Elevation Myocardial Infarction: A True or False Association - Ifedili, Ikechukwu (Perm J, 2019)
INTRODUCTION: Every year, more than 500,000 US Emergency Department visits are associated with cocaine use. People who use cocaine tend to have a lower incidence of true ST-elevation myocardial infarction (STEMI). OBJECTIVE: To identify the factors associated with true STEMI in patients with cocaine-positive (CPos) findings. METHODS: We retrospectively analyzed 1144 consecutive patients with STEMI between 2008 and 2013. True STEMI was defined as having a culprit lesion on coronary angiogram. Multivariate and univariate analyses were used to identify risk factors and create a predictive model. RESULTS: A total of 64 patients with suspected STEMI were CPos (mean age 53.1 ± 11.2 years; male = 80%). True STEMI was diagnosed in 34 patients. Patients with CPos true STEMI were more likely to be uninsured than those with false STEMI (61.8% vs 34.5%, p = 0.03) and have higher peak troponin levels (21.1 ng/mL vs 2.12 ng/mL, p = < 0.01) with no difference in mean age between the 2 groups (p = 0.24). In multivariate analyses, independent predictors of true STEMI in patients with CPos findings included age older than 65 years (odds ratio [OR] = 19.3, 95% confidence iterval [CI] = 1.2–318.3), lack of health insurance (OR = 4.9, 95% CI = 1.2–19.6), and troponin level higher than 0.05 (OR = 24.0, 95% CI = 2.6–216.8) (all p < 0.05). A multivariate risk score created with a C-statistic of 82% (95% CI = 71–93) significantly improved the identification of patients with true STEMI. CONCLUSION: Among those with suspected STEMI, patients with CPos findings had a higher incidence of false STEMI. Older age, lack of health insurance, and troponin levels outside of defined limits were associated with true STEMI in this group.